Analisis Tarif Angkutan Umum Bus Jurusan Terboyo Semarang Tirtonadi Solo Berdasarkan Biaya Operasional Kendaraan ( PO. ROYAL SAFARI ) - antika, lincah nur; supoyo, supoyo (Teknika, 2017)
AbstractTransportation is a pre-system / means to support community / population activities for economic activities. The important role of goods and human transport modes that connect from one place to another is public transportation, because public transport plays an important role in the world economy of society. Public transportation must provide fast, safe, comfortable, efficient and inexpensive services because good service is very influential for users of transportation services. In addition, in the world of transportation and public transportation tariffs are a matter of considerable consideration, because the determination of tariffs for public transport is a very interesting matter to be studied extensively so as not to cause losses between providers and users of public transport services. Determination of dance transport requires special treatment to react to it, therefore the determination of tariffs by analyzing based on Vehicle Operating Costs with primary and secondary data obtained directly from the field and companies from service providers, namely from Royal Safari Otomotif Company at a price of Rp. 1,350,000,000, - / bus. From analyzing based on Vehicle Operating Costs, it is expected to be able to provide benefits to providers and service users. The results of this data analysis Bus at a price of Rp. 1.350.000.000, - / bus shows that the public transport tariff based on Vehicle Operating Costs obtained is Rp.942,471,848.57, - per year or Rp.148.19, - per km-seat. Using the assumption of a 70% load factor of Rp.211.69, - per km-seat or basic tariff of Rp.22,439.14, - per seat with a distance of 106 km (Terboyo Semarang - Tirtonadi Solo). Taking into account the 30% profit for entrepreneurs on the Semarang - Tirtonadi Solo Terboyo route, the tariffs from the current analysis of vehicle operational costs with bus vehicles (in 2017) are Rp. 30,000, - per seat with a distance of 106 km. Bus Vehicle Public Transport Business from Otomotif Company. The Royal Safari is feasible to run because PBP